Pension Inequality and Collective Pensions Funds: The Trade-Offs of Pension Redistribution - Caputo-Galarce, R; Ordonez-Jofre, F (Routledge, 2025)
This paper evaluates the macroeconomic and welfare impacts of introducing a Collective Defined Contribution (CDC) scheme to reduce pension inequality within a Fully Funded Defined Contribution (FDC) system. Using an overlapping generations (OLG) model, we analyse the Chilean pension system to assess how a CDC scheme reallocates resources from high- to low-productivity pensioners, increasing overall welfare by improving the replacement rates of low-income retirees. Results show that implementing a CDC scheme boosts the capital stock and GDP while only slightly decreasing private savings and consumption. Although high-productivity workers experience a welfare loss due to increased contributions, the positive redistribution effect for low-productivity workers results in a net welfare gain for society. When compared to raising taxes on labour, capital, or consumption, the CDC scheme proves more efficient, as tax-based alternatives lead to larger welfare losses. Capital taxes significantly reduce investment and GDP, causing a 6.9% drop in steady-state consumption. Our findings are robust across different worker ratios, demonstrating that the CDC scheme is an effective policy for reducing pension inequality while supporting economic growth and maintaining overall welfare. © 2024 Informa UK Limited, trading as Taylor & Francis Group.